2018
DOI: 10.20517/2574-1209.2017.38
|View full text |Cite
|
Sign up to set email alerts
|

Temporizing amplatzer closure of an aorto-enteric fistula associated with a blind aortic stump via a translumbar approach

Abstract: We present a case of an aorto-enteric fistula (AEF) with chronic, persistent bleeding from a blind aortic stump managed by endovascular means. This novel approach may have extended the life of a patient who would otherwise have been subject to a high perioperative morbidity or persistent bleeding and death. While our patient ultimately expired, we believe this technique can be considered for temporization in highly-selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The choice of embolization device merits consideration. In the present case, but also in the cases described by others (Marone et al 2012;Wang et al 2018), an Amplatzer plug was used. This plug needs a larger access (8/9F), but has the advantage of a more rapid procedure with faster cessation of bleeding and less risk of migration.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The choice of embolization device merits consideration. In the present case, but also in the cases described by others (Marone et al 2012;Wang et al 2018), an Amplatzer plug was used. This plug needs a larger access (8/9F), but has the advantage of a more rapid procedure with faster cessation of bleeding and less risk of migration.…”
Section: Discussionmentioning
confidence: 77%
“…Literature search revealed three cases in which endovascular treatment of aortic stump blow-out has been described (Marone et al 2012;Wang et al 2018;Terasaki et al 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of these coils was due to their efficacy in occluding the opening in the distal aorta. Moreover, Wang et al 7 has shown this similar procedure done as means of palliation.…”
Section: Discussionmentioning
confidence: 93%